Qiwama dalam Rumah Tangga Perspektif Teori Mubadalah dan Relevansinya di Indonesia - Siti Khoirotul Ula (MAHAKIM Journal of Islamic Family Law, 2021)
In classical jurisprudence, the issue of Qiwāma -leadership and family protection is under the control of husbands and wives who are obliged to obey their husbands with the consequences that if there is disobedience from the wife- the husband has the right to educate her by advising, separating her (separating the bed), and beating her in a way that doesn't hurt. This understanding is based on the interpretation of the scholars of Surah an-Nisa 'verse 34. The rules in Indonesia, it is Law No.1 of 1974 concerning Marriage also state that the husband is the head of the family and wife is the housewife as a legalization of this interpretation. However, this Qiwāma does not always run according to the existing rules. In practice, many wives should had be a leader on their family while her husband lives. It caused Muslim feminist figures inIndonesia, Faqihuddin Abdul Kodir, spoken about the mubadalah theory, as a reinterpretation of classical fiqh constructions on gender equality. This article explain how the concept of qiwāma in the perspective of mubadalah and relevance in Indonesia. This is a report from literature research which is based on primary and secondary data sources in the form of documentary studies. The conclution in a husband and wife relationship should have understanding that they are on mutually relation. Whether, about matter of living or sexual services, both of them as partners, they have the same rights and obligations. The dominant relationship will be lostbecause of this reciprocality. They are responsible for mu'asyaroh bil ma'ruf to their partner and must maintain the dignity of each other's humanity. Therefor, the relevance of this theory, it should be our tradition for a long time, the mutual relation between husbands and wives in life has long been practiced by our agrarian culture.